A fully integrated approach through petrophysical analysis, hydraulic flow units and seismic inversion to map good quality flow unit of globigerina limestone gas reservoir in C field, Madura Straits. Issue 1 (July 2020) - Himawan, H; Haris, A; Riyanto, A
Abstract: The common problem for reservoir characterization usually related to understanding of vertical and lateral heterogeneity of reservoir. Understanding the vertical reservoir heterogeneity generally can be solved based on petrophysical analysis combined with hydraulic flow unit analysis result. HFU's analysis based on indicator of flow zone which reflect to rock quality that influenced by the mineralogical composition and texture of lithology. Whereas to understand the lateral heterogeneity, generally solve based on the quantitative seismic analysis as results from model based seismic inversion. The purpose of this study is to determine the lateral good flow unit distribution so that the development well placement and targets can be optimized. The petrophysical results obtain 370.5ftMD gross thickness with net pay = 346.0 ftMD, NtG = 93.4 %, Vclay = 6.9 %, Phie = 38.7 %, permeability = 22.6 mD and Sw = 46.6 %. From hydraulic flow units results obtain five flow units with the fifth flow unit has best quality. Characteristics of the fifth flow unit has FZI = 0.727, Vclay = 3.9 %, Phie = 45.1 %, Permeability = 229.6 mD and Sw = 31.1 %, with grainstone as dominant lithology. The good flow units have AI value 3600–4300 gr/cc*m/s and have lateral distribution relatively Northwest–Southeast. Going to the crest of structure, the thickness of good flow unit will be thinner because it is truncated by the fault.